IDDF2018-ABS-0036 MIR-632-inhibitor attenuates gastric cancer progression by suppressing angiogenesis in a TFF1-dependent manner. (June 2018) - Shi, Ying; Huang, Xiaoxiao; Chen, Guobin; Liu, Jingjing; Guleng, Bayasi; Ren, Jianlin
Abstract : Background: Gastric cancer (GC) is a common malignant disease worldwide. Aberrant miRNAs contribute to cells malignant behaviour, and targeted miRNAs have the potential ability in preclinical development to improve GC therapy. Our present studies demonstrated that miR-632-inhibitor attenuates GC progression in a trefoil factor 1 (TFF1)-dependent manner. Methods: We collected GC tissues and plasma samples to detect the expression of miR-632 by using real-time PCR. Dual luciferase reporter assay was used to identify that miR-632 regulate TFF1 expression directly. Gene array, western blot and in situ hybridization assays were performed to detect the angiogenesis and endothelial recruitment markers which were affected by miR-632. In addition, candidates of histones regulating miR-632 were detected in GC cells. Results: We found that miR-632 highly expressed in GC tissues and plasma (Fig.A) and identified that miR-632-inhibitor worked against tumour angiogenesis and endothelial recruitment by negatively regulated TFF1 expression (Fig.B-E). Recombinant protein of TFF1 reversed the angiogenesis increased by miR-632. We also found that miR-632 affected angiogenesis marker CD34 and MMP9 (Fig.F) and was degraded by histones H3K4 me3 and H3K27ac. Conclusions: Thus, our study demonstrated that miR-632-inhibitor attenuates gastric cancer progression by suppressing angiogenesis in a TFF1-dependent manner. miR-632-inhibitor may be as a novel therapeutic approach for GC patients.